1993
DOI: 10.2527/1993.7161561x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the control of litter size in swine: I. Comparative studies on in vitro development of Meishan and Yorkshire preimplantation embryos

Abstract: Three experiments were conducted to examine the in vitro development of preimplantation embryos from the prolific Chinese Meishan pig. Experiment 1 was conducted to assess whether Meishan embryos would develop in vitro and retain their viability, whereas Exp. 2 and 3 examined the developmental pattern of Meishan embryos. In all three experiments, Yorkshire embryos served as a contemporary comparison. Ovulation and embryo recovery rates were not different between Meishan and Yorkshire gilts. Meishan embryos cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 15 publications
2
54
0
1
Order By: Relevance
“…In the study of Youngs et al (1993), the Meishan pig can farrow three to five more live pigs per litter than Western breeds Youngs et al, 1993). Wilson found that the Meishan placenta exhibits a marked and progressive increase in the density of blood vessels on the placental surface .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Youngs et al (1993), the Meishan pig can farrow three to five more live pigs per litter than Western breeds Youngs et al, 1993). Wilson found that the Meishan placenta exhibits a marked and progressive increase in the density of blood vessels on the placental surface .…”
Section: Discussionmentioning
confidence: 99%
“…With fertilization rates close to 95% [5][6][7][8], the number early embryos can potentially reach around 20. However, by the time of farrowing, litter size is reduced down to 10 to 13 piglets/sow [9].…”
Section: Introductionmentioning
confidence: 99%
“…Little research has been conducted on in vitro development of Meishan embryos. Youngs et al (1993) reported that Meishan embryos developed slower than embryos from Yorkshire females, zia uitro. Slower embryo development was associated with less estradiol-17p production from earlier maturing Meishan blastocysts which lengthened the optimal window of uterine receptivity allowing more later maturing Meishan than Yorkshire blastocysts to survive.…”
Section: Introductionmentioning
confidence: 99%